First case of childhood Takayasu arteritis with renal artery aneurysms - Rajhi Hatem; Bachrouche Haythem; Harrath Mouna; Gargah Tahar; Abdallah Taeb; Lakhoua Mohamed R (BMC, 2010)
Abstract Takayasu arteritis is a large vessel systemic granulomatous vasculitis characterized by stenosis or obliteration of large and medium sized arteries. It commonly involves elastic arteries such as the aorta and its main branches. Renal artery involvement is rare and has not been reported in a child. We report a 12-year-old boy with Takayasu arteritis who developed severe hypertension, proteinuria, microscopic hematuria and renal dysfunction. Conventional angiography demonstrated aneurysms of both renal arteries and multiple microaneurysms of the superior mesenteric artery. This case report illustrates that the children with Takayasu arteritis can develop renal involvement resulting in hematuria, proteinuria and even renal failure.